2011
DOI: 10.1016/j.ejcb.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Flanking genes of an essential gene give information about the evolution of metazoa

Abstract: a b s t r a c tWe collected as much information as possible on new lamin genes and their flanking genes. The number of lamin genes varies from 1 to 4 depending more or less on the phylogenetic position of the species. Strong genome drift is recognised by fewer and unusually placed introns and a change in flanking genes. This applies to the nematode Caenorhabditis elegans, the insect Drosophila melanogaster, the urochordate Ciona intestinalis, the annelid Capitella teleta and the planaria Schmidtea mediterranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Because these proteins, especially the components of PRC2, are bound by many lncRNAs, we speculated that not all of the low-scoring hits were functionally irrelevant. A popular method to roughly determine whether a DNA sequence is functional is to evaluate its conserved context [45-47]. We examined the hits of all of the queries in human, chimpanzee, mouse, rat and platypus.…”
Section: Resultsmentioning
confidence: 99%
“…Because these proteins, especially the components of PRC2, are bound by many lncRNAs, we speculated that not all of the low-scoring hits were functionally irrelevant. A popular method to roughly determine whether a DNA sequence is functional is to evaluate its conserved context [45-47]. We examined the hits of all of the queries in human, chimpanzee, mouse, rat and platypus.…”
Section: Resultsmentioning
confidence: 99%
“…2). Whereas the nuclear localization signal in bilateral metazoa involves 4 consecutive basic residues, the lamins from the two species of the radiata currently known show only 3 basic residues in the sequences KRSR (Hydra) and KRAR (Nematostella) (Zimek and Weber, 2011). The deduced protein sequence of 760 amino acids corresponds to a size of 85.4 kDa and shows a length like in protostomic metazoa (Zimek and Weber, 2008).…”
Section: Identification Of a Cytoplasmic Nematostella If Proteinmentioning
confidence: 97%
“…Because of the closeness of these values it is currently impossible to decide which mammalian IF protein is the obvious counterpart of Nematostella IF cytovec. Attempts to get information via flanking genes as previously done for lamin genes (Zimek and Weber, 2011) were not possible because of the gaps in the genome of Nematostella. We note however that in the primitive bilateral animal, the nematode C. elegans, there is firm in vivo and in vitro evidence for a keratin-like obligatory heteropolymer system, but no indication for an additional homopolymer system (Karabinos et al, 2003).…”
Section: Identification Of a Cytoplasmic Nematostella If Proteinmentioning
confidence: 99%
“…LMNB1 encodes lamin B1, and LMNB2 encodes lamins B2 and B3. An evolutionary study of lamins suggested that all metazoan cells have at least one B-type lamin, and LMNB1 is the most ancient and conserved form of the lamin gene [43].…”
Section: The Nuclear Laminamentioning
confidence: 99%